2009
DOI: 10.1007/s10562-009-9924-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep Oxidation of Benzene on Pt/V2O5–TiO2 Catalysts

Abstract: The combustion of benzene was studied on Pt supported on V 2 O 5 -TiO 2 samples containing different amounts of V 2 O 5 . Vanadium was highly dispersed as V 4? for low V 2 O 5 loadings, forming a vanadia monolayer on titanium dioxide for a V 2 O 5 concentration of about 5%wt. V 2 O 5 -TiO 2 samples were more active than V 2 O 5 and TiO 2 single oxides, and the activity increased with the vanadia content. The platinum dispersion in Pt/V 2 O 5 -TiO 2 catalysts increased with the V 2 O 5 loading but the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Additional experiments have to be done to evaluate quantitatively the Pt dispersion in order to validate this assumption. According to Garetto et al [18], the sample YSZ-60 nm exhibits similar catalytic performances as Pt-supported on alumina containing 0.33 wt% Pt (table 1). The apparent activation energy (Ea) was obtained via an Arrhenius-type analysis, by plotting ln r values as a function of 1/T.…”
Section: Propane Combustion On Pt/yszmentioning
confidence: 78%
“…Additional experiments have to be done to evaluate quantitatively the Pt dispersion in order to validate this assumption. According to Garetto et al [18], the sample YSZ-60 nm exhibits similar catalytic performances as Pt-supported on alumina containing 0.33 wt% Pt (table 1). The apparent activation energy (Ea) was obtained via an Arrhenius-type analysis, by plotting ln r values as a function of 1/T.…”
Section: Propane Combustion On Pt/yszmentioning
confidence: 78%
“…In particular, Garcia et al [9] proposed that the increased activity for propane combustion on Pd/ V 2 O 5 -Al 2 O 3 catalysts is related to the modified redox properties of the catalysts. Recently, we studied the benzene combustion on Pt/V 2 O 5 -TiO 2 catalysts [10]. We found that the Pt dispersion on Pt/V 2 O 5 -TiO 2 increases with the V 2 O 5 content but the benzene combustion turnover rate follows an opposite trend.…”
Section: Introductionmentioning
confidence: 97%
“…Platinum and palladium supported on alumina carriers are widely employed for the combustion of non-halogenated hydrocarbons [1][2][3]. However, stable lower alkanes such as propane require relatively high temperatures to be completely oxidized over conventional Pt(Pd)/Al 2 O 3 and increasing research work has been lately undertaken to find suitable supports or promoters for improving the intrinsic metal oxidation activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is so even for the most active catalysts like supported Pd and/or Pt. 8,9 In terms of elementary steps, the low activity is related to the difficulty associated with the dissociative adsorption of methane on catalyst surfaces. 10 The sticking probability of methane on noble metals is low, 11 and in addition, methane dissociation is strongly dependent on the surface coverage of reaction intermediates.…”
Section: Introductionmentioning
confidence: 99%